Khachkars in Adana Museum - Ayşe Aydın (Art-Sanat)
The khachkars, peculiar to Armenians, have a significant place in Byzantine art. The khachkars, which can be seen since the 4th century and are still produced today, have many functions. They were usually used for protection on the facades and the courtyard walls of religious buildings and were also designed as tombstones or in memory of important events and people. The cross on the khachkar is often depicted as the Tree of Life. Below the vertical arm of the cross, palmette/ palm leaves develop sideways. The cross is located on a stepped pedestal symbolising Golgotha or on a rosette symbolising abundance. There are four marble khachkars in Adana Museum. According to the motif and stylistic features of the decoration program, they are produced between the 11th and 13th centuries. Taking into consideration the few in situ khachkars in the region, it can be said that khachkars in Adana Museum were also used in castles, churches and chapels. The motifs and stylistic features of the khachkars of the 11th-13th centuries are similar to the Anatolian Seljuk decoration program. The reason for this is that the Armenian craftsmen, who also worked in the building of Seljuk structures, included floral and geometric elements of Seljuks in their works and interpreted them with some additions. This interaction is observable in the floral decorations and the geometric decorations designed with the principle of infinity, together with their symbolic meanings on the khachkars in the Adana Museum.